2012
DOI: 10.1002/ejoc.201201269
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Rearrangement of Azido Ketones into Oxazoles via Azirines: One‐Pot, Metal‐Free Heteroannulation to Functionalized 1,3‐Oxazoles

Abstract: α‐Azidoacetophenones were converted into 2‐aryl‐1,3‐oxazole‐4‐carbaldehydes through rearrangement of the carbon framework upon exposure to DMF/POCl3. The unprecedented rearrangement occurs via alkenyl azides and 2H‐azirines. A mechanism for this unusual reaction was proposed and evidenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…. In recent years, many strategies have been developed on the synthesis of oxazole compounds, such as condensations, cyclizations, transition-metal-catalyzed addition of diazo compounds to nitriles, and rearrangements . Despite the exciting achievements on the synthesis of oxazole derivatives, the exploration of expedient and novel methods for the construction of oxazole derivatives is still commercioganic.…”
mentioning
confidence: 99%
“…. In recent years, many strategies have been developed on the synthesis of oxazole compounds, such as condensations, cyclizations, transition-metal-catalyzed addition of diazo compounds to nitriles, and rearrangements . Despite the exciting achievements on the synthesis of oxazole derivatives, the exploration of expedient and novel methods for the construction of oxazole derivatives is still commercioganic.…”
mentioning
confidence: 99%
“…Shah et al reported another similar type of microwave‐assisted 2 H ‐aziridine formation reaction. Thermal rearrangement of α‐azidoacetophenone into alkenyl azide, 2‐aryl‐1,3‐oxazole‐4‐carbaldehyde is produced by rearrangement of the carbon skeleton when exposed to DMF‐POCl 3 (Scheme 57) [77].…”
Section: Decomposition Of Vinyl Azidesmentioning
confidence: 99%
“…Representative flexi-arm tripodal host molecules 6a,c In continuation of our interest in C 3 -symmetric compounds 12 in biologically potent compounds 13 and in oxazole chemistry, 14 we report herein the synthesis and study of flexible tripodal 1,3-oxazoles by employing 1,3,5-trimethylbenzene as the substrate for transformation into C 3 -symmetric scaffolds.…”
Section: Figurementioning
confidence: 99%